Salivary IgA and pre-training wellness status across an international soccer qualifying and finals campaign (Euro 2016). Issue 5 (October 2018) - Owen, Adam L; Morgans, Ryland; Kavanagh, Ronan; Djaoui, Leo
The aim of this investigation was to examine the salivary IgA (salivary immunoglobulin-A), RPE and pre-training wellness status across an international qualification and finals campaign. Data were collected for 37 elite male international soccer players (mean ± standard deviation, age: 24.9 ± 3.3 years; height: 182.5 ± 6 cm; mass: 73.1 ± 6.2 kg; positions: Goalkeeper, Center Defender, Wide Defender, Center Midfield, Wide Forward, and Center Forward) across two consecutive seasons. Training RPE, wellness questionnaire, and saliva samples were taken throughout the Euro 2016 qualifying and finals campaign. Results revealed how Readiness and Total Wellness (r = −0.28, p < 0.05) correlated to salivary immunoglobulin-A, in the day preceding games (MD−1). No correlation between wellness and salivary immunoglobulin-A was observed in MD−4; however, Energy correlated to salivary immunoglobulin-A between MD−3 and MD (from r = −0.18 to −0.22, p < 0.05), with significance observed between RPE and Total Wellness r = −0.22 (Total Wellness), r = −0.21 (Energy), r = −0.17 (Readiness), and r = −0.24 (Lower Body Soreness) (p < 0.05). It can be concluded from the data that all wellness markers except Sleep correlated to salivary immunoglobulin-A. Furthermore, it was revealed that Energy appeared to be the greatest wellness assessment marker related to salivary immunoglobulin-A. As a result of this specific investigation, it can be confirmed that the use of a pre-training subjective Wellness questionnaires may be a useful tool to monitor individual mucosal immunity response to training.